Musyawarah Sebuah Proses Deliberasi Dalam Layanan Konseling - Arina Mufrihah; Fitri Aulia (Universitas Hamzanwadi, 2018)
This research aimed to understand the interpretation of surah al-Quran related to musyawarah as problem solving and how to apply the surah interpretation as resource for counselors and counselees to communicate each other. Librabry technique method was used to find, analyse, and understand the relevant surah and ayah. The Book of Tafsir al-Misbah by Professor M. Quraish Shihab used as the main resource and The Meaning of The Glorious Quran Text, Translation Commentry by Yusuf Abdullah Ali as the secondary resource. Meanwhile the Book of Fathul al-Rahman used to discover various ayah mentioning and talking about musyawarah. The concept of musyawarah at least found in two surah of al-Quran, first is surah asy-Syuraa: 38 and second is surah Al ‘Imran: 159. These two surah have a time contextuality to use as a counseling skill and a relationship form of counseling. Musyawarah can be be part of counseling service as the helping relationship and the helping profession. Through interpreting the surah, the whole understanding could be concluded that musyawarah is a deliberative method to solve people’s problem. The best result of doing musyawarah can be created because people who do musyawarah will choose a good communication, meekly talk, not egoistic, willing to apologize each other, open minded, and asking maghfira and forgiveness from Allah.